Bacillus subtilis 29784 induces a shift in broiler gut microbiome toward butyrate-producing bacteria and improves intestinal histomorphology and animal performance. (18th January 2019) - Jacquier, V; Nelson, A; Jlali, M; Rhayat, L; Brinch, K S; Devillard, E
ABSTRACT: The study reports the effects of Bacillus subtilis 29784 on broiler performance. A total of 1, 600 one-day-old Cobb 500 male broiler chicks received either a control diet or the same diet to which B. subtilis 29784 spores were added (1E8 CFU/kg of feed). The birds were slaughtered at 42 D of age. Ileal and cecal tissues and content were collected for histomorphological analysis and 16S rRNA gene sequencing, respectively. The inclusion of B. subtilis 29784 led to an increase of final body weight gain of broilers (+5.7%; P < 0.0001) and an improvement in feed conversion ratio (–5.4%; P < 0.0001). Higher feed efficiency in the Bacillus -fed group was correlated with a significant increase in intestinal microvilli length (+18% in ileum and +17% in cecum; P < 0.001). Among the differences revealed by 16S rRNA analysis, Ruminococcus, Lachnoclostridium, and Anaerostipes were found in higher relative abundance in Bacillus -treated birds at the cecal level. These bacterial genera include species that produce butyrate, the main source of energy for enterocytes and known to be an immune modulator. There was also a slight increase in the Butyrivibrio genus in the cecum, which is known to be an important player in the production of conjugated linoleic acid, also considered an anti-inflammatory compound. In conclusion, dietary supplementation of B. subtilis 29784 significantly improved the growth performance of broilers, likely through beneficial effects on microbiota and host.